Making Connections: Traditional Folktales from the Ao and Angami Communities in Nagaland, India and Contemporary Narratives of Globalization - Peh, Yang Yu (2016)
This project aims to raise awareness of ongoing contemporary issues in the era of globalization confronted by the Angami and the Ao tribes, minority communities in Nagaland. Our folktales will be analyzed as to how cultural values can be reflected through art. Connections will then be made between cultural values of the tribe and globalization today. The research especially targets the younger generation of Naga's. [1st Award]